FIRST REPORT ON SURFACE ASPECTS OF Mansonella ozzardi (SPIRURIDA: ONCHOCERCIDAE) MICROFILARIAE BY SCANNING ELECTRON MICROSCOPY: PRELIMINARY RESULTS - Leite Adami, Yara; Menezes de Oliveira, Aleksandra; Marize Lanfredi (in memorian), Reinalda; Maia-Herzog, Marilza (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Blood samples from Mansonella ozzardi infected volunteers from Vila Antimary (Amazonas State) were processed and a protocol to isolate and prepare microfilariae was carried out in order to perform Scanning Electron Microscopy (SEM) analysis. Data obtained from ultrastructure showed some undescribed structural points of the parasite such as a dimple in the anterior end of the larva and small points –orifice-like– that may be related to amphidial structures or simply pores. Another interesting feature was the tip of the tail which is very similar to that found in the rodent parasite Dunnifilaria meningica.